2016
DOI: 10.5152/tud.2016.90836
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibilities of Escherichia coli isolates as agents of community-acquired urinary tract infection (2008-2014)

Abstract: Objective: Urinary tract infections (UTIs) are among the most frequently seen community-acquired infections worldwide. E. coli causes 90% of urinary system infections. To guide the empirical therapy, the resistance pattern of E. coli responsible for community-acquired UTI was evaluated throughout a seven-year period in this study. Material and methods:The urine cultures of patients with urinary tract infections admitted to outpatient clinics between 1 st January 2008 and 31 st December 2014 were analyzed. Pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
7
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 15 publications
8
35
7
5
Order By: Relevance
“…This agent is well tolerated and has a few side effects. It has an increased role as a therapeutic option against multidrug-resistant Enterobacteriaceae (19,20,22,23). Cumulative susceptibility of fosfomycin against ESBL positive Enterobacteriaceae is reported as 87.7% according to CLSI criteria (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This agent is well tolerated and has a few side effects. It has an increased role as a therapeutic option against multidrug-resistant Enterobacteriaceae (19,20,22,23). Cumulative susceptibility of fosfomycin against ESBL positive Enterobacteriaceae is reported as 87.7% according to CLSI criteria (24).…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative susceptibility of fosfomycin against ESBL positive Enterobacteriaceae is reported as 87.7% according to CLSI criteria (24). However, lower susceptibility rates (<50%) was showed in some studies, and in a study this agent was shown to be active against only 50% of Klebsiella (22,25).…”
Section: Discussionmentioning
confidence: 99%
“…[4,5,16] Based on the 2013 data released by National Antimicrobial Resistance Surveillance System (UAMDS) in Turkey, ESBL-producing strains were detected in 44.9% of E. coli, and 49.9% of K. pneumoniae isolates. In our study the most frequent microbial agent was E. coli (63.1%).…”
Section: Discussionmentioning
confidence: 99%
“…[4] In recent studies, extended-spectrum beta-lactamase (ESBL) producing strains have been detected in E.coli isolates at a higher frequency, both in the world, and in our country. [5,6] In the treatment of the infections caused by ESBL -producing strains, inadequacy of the antibiotics other than carbanepems in addition to their higher mortality rates have been also indicated. [7] However, together with increased resistance of members of Enterobacteriaceae family, and P. aeruginosa isolates against carbapenems, ways of using carbapenems at a lesser frequency have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Kimi zaman klinik gereklilik nedeniyle 21 güne kadar uzayabilmektedir (6) . GSBL üreten Gram negatif enterik çomakların hem toplum kaynaklı hem de hastane kaynaklı enfeksiyonlarındaki artış, aşırı karbapenem kullanımına neden olmaktadır ve buna bağlı olarak karbapenemlere dirençli Gram negatif enterik çomakların sıklığında artış saptanmaktadır (7)(8)(9) . Ayrıca ülkemizde karbapenemlerin yalnızca hastanede kullanımının ruhsatlı olması, hastanede yatış süresinin uzamasına ve maliyet artışına neden olmaktadır.…”
Section: Introductionunclassified